‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Impact of Eighteen Degree Water thickness variation on the thermal and biogeochemical structure in the euphotic layer - Hatsumi Nishikawa; Eitarou Oka; Shusaku Sugimoto; Fumiaki Kobashi; Masao Ishii; Nicholas R. Bates (Journal of Oceanography, 2025)
It has been recently found that North Pacific Subtropical Mode Water impacts the overlying thermal structure by uplifting the isotherms when it thickens. How the thickness variation of North Atlantic Subtropical Mode Water, also known as Eighteen Degree Water (EDW), affects the overlying thermal and biogeochemical structure through such uplifting effect has been investigated using Argo float data and shipboard observation data at Bermuda Atlantic Time-series Study site. When EDW was thicker, the overlying isotherms were uplifted, leading to a decrease in temperature centered at 50–100 dbar in the warm season; in addition, the oxycline existing around 100 dbar and the nitracline at 100–150 dbar also tended to be uplifted, leading to an increase of apparent oxygen utilization and nitrate concentrations in the lower euphotic layer; furthermore, there is a tendency that chlorophyll- a maximum around 100 dbar shallowed, and primary production integrated in the euphotic layer increased during the spring bloom season. Thus, although the core of thicker EDW tends to have less nitrate as shown by previous studies, thicker EDW tends to increase biological production in the euphotic layer through the enhanced uplifting effect.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Monitoring Impacts of the Gulf Stream and its Rings on the Physics, Chemistry, and Biology of the Middle Atlantic Bight Shelf and Slope from CMV Oleander - Magdalena Andres; Thomas Rossby; Eric Firing; Charles Flagg; Nicholas Bates; Julia Hummon; Denis Pierro; Timothy Noyes; Matthew Enright; Jeffery O’Brien; Rebecca Hudak; Shenfu Dong; et al. (Oceanography, 2025)
Sustained observation is key to measuring physical and ecological variability in the Northwest Atlantic. Here we illustrate how a partnership with a merchant marine container vessel in service between New Jersey and Bermuda twice per week gives scientists a unique window into upper ocean currents, water properties, and marine ecology. Scientific observations collected from CMV Oleander, operated by Bermuda Container Line/Neptune Group, enable cross-disciplinary research, complement satellite measurements, and contribute to global observing programs—including the Global eXpendable BathyThermograph (XBT) Network, the Surface Ocean CO2 Atlas (SOCAT), and the Continuous Plankton Recorder (CPR) Survey. Recent co-located measurements along the Oleander Line document that fronts in temperature, salinity, and carbon dioxide concentrations align with the (sub)mesoscale circulation patterns. The sustained observations show warming and shrinking of the Slope Sea, a northward shift of the Gulf Stream, and warming of the “18°C water” (subtropical North Atlantic mode water) to 19°C.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Investigating Labrador Sea's persistent surface O2 anomaly using observations and biogeochemical model results - Amavi N. Silva; Duncan A. Purdie; Nicholas R. Bates; Toby Tyrrell (Journal of Marine Systems, 2024)

Calcification and trophic responses of mesophotic reefs to carbonate chemistry variability - Timothy J. Noyes; Rebecca Garley; Nicholas R. Bates (Frontiers in Marine Science, 2024)
Mesophotic coral ecosystems (MCEs) are extensions of adjacent shallow water coral reefs. Accessibility to these ecosystems is challenging due to their depth limits (~ 30 – 150 m) and as a result, scientific knowledge of these reef systems is limited. It has been posited that the depth limits of MCEs diminish anthropogenic effects experienced by shallow reef systems. A lack of empirical measurements to date has made this hypothesis impossible to determine for mesophotic reef metabolism. The alkalinity anomaly technique was utilized to determine rates of net ecosystem calcification (NEC) and net ecosystem production (NEP) from 30, 40 and 60 m mesophotic reefs during a 15-month period. Seawater chemistry was determined to be chemically conducive for calcification (average aragonite saturation Ω aragonite of 3.58, average calcite saturation Ω calcite of 5.44) with estimates of NEC indicating these reef systems were net accretive and within global average values for shallow coral reefs (< 30 m). The strongest periods of calcification occurred in late summer and were coupled with strong autotrophic signals. These episodes were followed by suppressed calcification and autotrophy and in the case of the 60 m reefs, a switch to heterotrophy. Whilst there was variability between the three reefs depths, the overall status of the mesophotic system was net autotrophic. This determination was the opposite of trophic status estimates previously described for adjacent shallow reefs. Whilst there were periods of net dissolution, the mesophotic reef system was net accretive (i.e., gross calcification > gross CaCO 3 dissolution). The measured inorganic carbon chemistry and estimates of NEC and NEP represent the first such biogeochemical measurements for MCEs. The values established by this study demonstrate just how close these understudied ecosystems are in terms of the known boundary thresholds for low saturation state reefs. Making predictions on how these ecosystems will respond to future climatic conditions, will require greater sampling effort over long times scales to decouple the environmental controls exerted on such ecosystems.

Forty years of ocean acidification observations (1983–2023) in the Sargasso Sea at the Bermuda Atlantic Time-series Study site - Nicholas R. Bates; Rodney J. Johnson (Frontiers in Marine Science, 2023)
Ocean physical and biogeochemical conditions are rapidly changing over time. Forty years of observations from 1983 to 2023 collected at the Bermuda Atlantic Time-series Study (BATS) site near Bermuda in the North Atlantic Ocean shows continuing trends of surface warming, increase in salinity, loss of dissolved oxygen (DO), increase in carbon dioxide (CO 2 ), and ocean acidification (OA) effects. Over this period, the ocean has warmed by about +1°C, increased in salinity by +0.136, and lost DO by 12.5 µmol kg −1 or ~6%. Since the 1980s, ocean dissolved inorganic carbon (DIC), total alkalinity (TA), a tracer of anthropogenic CO 2 (C TrOCA ), and fugacities/partial pressures of CO 2 (i.e., f CO 2 and p CO 2 ) have continued to increase substantially, with no evidence of a reduction in the rates of change over time. Contemporaneously, ocean pH has decreased by ~0.1 pH units [with ocean acidity (i.e., H + ) increasing by >30%], and the saturation states of calcium carbonate minerals (Ω calcite and Ω aragonite ) have decreased. These OA indicators show that the chemical conditions for calcification have become less favorable over the past 40 years. Updating of data and trends at the BATS site show how ocean chemistry of the 2020s is now outside the range observed in the 1980s, and how essential these data are for predicting the response of ocean chemistry and marine ecosystems to future shifting earth and ocean conditions.

Advancing best practices for assessing trends of ocean acidification time series - Adrienne J. Sutton; Roman Battisti; Brendan Carter; Wiley Evans; Jan Newton; Simone Alin; Nicholas R. Bates; Wei-Jun Cai; Kim Currie; Richard A. Feely; Christopher Sabine; Toste Tanhua; et al. (Frontiers in Marine Science, 2022)
Assessing the status of ocean acidification across ocean and coastal waters requires standardized procedures at all levels of data collection, dissemination, and analysis. Standardized procedures for assuring quality and accessibility of ocean carbonate chemistry data are largely established, but a common set of best practices for ocean acidification trend analysis is needed to enable global time series comparisons, establish accurate records of change, and communicate the current status of ocean acidification within and outside the scientific community. Here we expand upon several published trend analysis techniques and package them into a set of best practices for assessing trends of ocean acidification time series. These best practices are best suited for time series capable of characterizing seasonal variability, typically those with sub-seasonal (ideally monthly or more frequent) data collection. Given ocean carbonate chemistry time series tend to be sparse and discontinuous, additional research is necessary to further advance these best practices to better address uncharacterized variability that can result from data discontinuities. This package of best practices and the associated open-source software for computing and reporting trends is aimed at helping expand the community of practice in ocean acidification trend analysis. A broad community of practice testing these and new techniques across different data sets will result in improvements and expansion of these best practices in the future.

Utilizing Experiment and Theory to Evaluate Rhodamine B ethylenediamine as a Fluorescent Sensor for G-type Nerve Agents - Anna Hamstra; Yajie Cai; Zachary Reynolds; Cody S. Griffins; Arnold L. Rheingold; Nicholas J. Schaaf; Ekkehard Sinn; Jefferson E. Bates; Aruna J. Weerasinghe (Journal of Fluorescence, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ocean Observing in the North Atlantic Subtropical Gyre - Nicholas Bates; Rodney Johnson (Oceanography, 2021)

Opportunities and challenges applying gene editing to specialty crops - Nicholas J. Bate; Christopher D. Dardick; Ruud A. de Maagd; Robert W. Williams (In Vitro Cellular & Developmental Biology - Plant, 2021)

Catchability of Atlantic salmon at high water temperatures: Implications for river closure temperature thresholds to catch and release angling - Travis E. Van Leeuwen; Brian Dempson; David Cote; Nicholas I. Kelly; Amanda E. Bates (Fisheries Management and Ecology, 2021)
Warming water temperatures, combined with increased mortality following catch and release, could have synergistic consequences if rivers remain open to catch and release at high water temperatures, and catchability of fish remains similar across water temperatures. Here archived data for Atlantic salmon, Salmo salar L., were used to (a) quantify the influence of water temperature on catchability and (b) refine estimates of absolute catch and release mortality to incorporate the relationship between temperature and catchability. A significant decline in the number of Atlantic salmon caught at warmer water temperatures was found after accounting for the effects of river water height, fishing effort, run duration and year‐to‐year differences in fish abundance. Overall, absolute catch and release mortalities were predicted to be infrequent at cool river temperatures. At river temperatures sometimes associated with fishing closures, mortality due to the catch and release ranged from 6% to 14%. Although post‐release mortality increases with water temperature, it is somewhat compensated by the reduced catchability of Atlantic salmon. Thus, the catchability component of catch and release is an integral consideration when evaluating the effectiveness of river closure temperature thresholds when managing catch and release angling.

Wavelet decomposition facilitates training on small datasets for medical image classification by deep learning - Axel H. Masquelin; Nicholas Cheney; C. Matthew Kinsey; Jason H. T. Bates (Histochemistry and Cell Biology, 2021)

High-throughput phenotypic screening of random genomic fragments in transgenic rice identified novel drought tolerance genes - Toshiyuki Komori; Yuejin Sun; Masakazu Kashihara; Natsuko Uekawa; Norio Kato; Satoru Usami; Noriko Ishikawa; Yukoh Hiei; Kei Kobayashi; Rise Kum; Esteban Bortiri; Kimberly White; et al. (Theoretical and Applied Genetics, 2020)

A Surface Ocean CO2 Reference Network, SOCONET and Associated Marine Boundary Layer CO2 Measurements - Rik Wanninkhof; Penelope A. Pickers; Abdirahman M. Omar; Adrienne Sutton; Akihiko Murata; Are Olsen; Britton B. Stephens; Bronte Tilbrook; David Munro; Denis Pierrot; Gregor Rehder; J. Magdalena Santana-Casiano; et al. (Frontiers in Marine Science, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Seawater Carbonate Chemistry Distributions Across the Eastern South Pacific Ocean Sampled as Part of the GEOTRACES Project and Changes in Marine Carbonate Chemistry Over the Past 20 Years - Nicholas Robert Bates (Frontiers in Marine Science, 2018)

Corrigendum: Depth Dependent Relationships between Temperature and Ocean Heterotrophic Prokaryotic Production - Christian Lønborg; L. Antonio Cuevas; Thomas Reinthaler; Gerhard J. Herndl; Josep M. Gasol; Xosé Anxelu G. Morán; Nicholas R. Bates; Xosé A. Álvarez-Salgado (Frontiers in Marine Science, 2017)

Long-term T-DNA insert stability and transgene expression consistency in field propagated sugarcane - Kerry Hosmer Caffall; Chengkun He; Michele Smith-Jones; Kristin Mayo; Pearl Mai; Shujie Dong; John Ke; Erik Dunder; Michele Yarnall; Rachel Whinna; Joe DeMaio; Weining Gu; et al. (Plant Molecular Biology, 2017)

Twenty Years of Marine Carbon Cycle Observations at Devils Hole Bermuda Provide Insights into Seasonal Hypoxia, Coral Reef Calcification, and Ocean Acidification - Nicholas R. Bates (Frontiers in Marine Science, 2017)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Depth Dependent Relationships between Temperature and Ocean Heterotrophic Prokaryotic Production - Christian Lønborg; L. Antonio Cuevas; Thomas Reinthaler; Gerhard J. Herndl; Josep M. Gasol; Xosé Anxelu G. Morán; Nicholas R. Bates; Xosé A. Álvarez-Salgado (Frontiers in Marine Science, 2016)

Assessing Ocean Acidification Variability in the Pacific-Arctic Region as Part of the Russian-American Long-term Census of the Arctic - Nicholas Bates (Oceanography, 2015)

A Time-Series View of Changing Ocean Chemistry Due to Ocean Uptake of Anthropogenic CO2 and Ocean Acidification - Nicholas Bates; Yrene Astor; Matthew Church; Kim Currie; John Dore; Melchor Gonaález-Dávila; Laura Lorenzoni; Frank Muller-Karger; Jon Olafsson; Magdalena Santa-Casiano (Oceanography, 2014)

The Ocean Carbon Cycle in the Western Arctic Ocean: Distributions and Air-Sea Fluxes of Carbon Dioxide - Nicholas Bates; Wei-Jun Cai; Jeremy Mathis (Oceanography, 2011)

Comparative genome organization reveals a single copy of CBF in the freezing tolerant crucifer Thlaspi arvense - Ning Zhou; Stephen J. Robinson; Terry Huebert; Nicholas J. Bate; Isobel A. P. Parkin (Plant Molecular Biology, 2007)

Determining net dissolved organic carbon production in the hydrographically complex western Arctic Ocean - Jeremy T. Mathis; Dennis A. Hansell; David Kadko; Nicholas R. Bates; Lee W. Cooper (Limnology and Oceanography, 2007)
Each spring and summer, the Chukchi Sea in the western Arctic Ocean experiences a short but intense phytoplankton bloom that is controlled by sea ice cover, nutrient availability, and river runoff. During the bloom, dissolved inorganic carbon (DIC) concentrations are drawn down in the mixed layer (shelf, ~Δ100 µmol kg −1 ; shelf‐break, ~Δ50 µmol kg −1 ; basin, −1 ) and converted to particulate organic carbon (POC) and dissolved organic carbon (DOC). We use δ 18 O and salinity to estimate DOC inputs by river and sea ice melt, allowing the marine portion of the DOC pool to be compared between seasons and to facilitate estimates of net DOC production in the region. We estimate that ~10% of the DIC consumed during net community production is converted to DOC. The remaining carbon deficit (90% of DIC drawdown) is most likely exported from the mixed layer as POC. In 2002 a carbon (C) mass balance was developed for the Chukchi Sea that showed that rates of vertical export were highest over the Chukchi Shelf near Point Barrow (64 mmol C m − d −1 ), but more commonly ranged from 10 to 35 mmol C m − d −1 over the remainder of the shelf. At the shelf‐break and in the Canada Basin export production was − d −1 . DOC plays a relatively small role as a carbon sink in the system, but quantifying its contributions provides more robust estimates of export production in the Arctic.

A ROS Repressor-mediated Binary Regulation System for Control of Gene Expression in Transgenic Plants - Ulrike A. Schäfer; Dwayne D. Hegedus; Nicholas J. Bate; Abdelali Hannoufa (Transgenic Research, 2004)

Seasonal variability of the effect of coral reefs on seawater CO2 and air—sea CO2 exchange - Nicholas R. Bates (Limnology and Oceanography, 2002)
There are complex physical and biological processes controlling the exchange of carbon dioxide (CO 2 ) between the ocean and atmosphere. In coral reef ecosystems, the balance of biological processes such as calcium carbonate (CaCO 3 ) formation and organic carbon production can either lead to CO 2 being retained in the oceanic environment (i.e., oceanic sink of CO 2 ) or returned to the atmosphere through gas exchange (oceanic source of CO 2 ). What remains uncertain is the fate of CO 2 in reefs subject to seasonal change and the annual balance of air—sea CO 2 flux in such systems. Here it is shown that the Bermuda coral reef acts as a sourc of CO 2 to seawater overlying the reef. The magnitude of this source of CO 2 varies seasonally in response to changes in the reef community between coral‐ and macroalga‐dominated states, reflecting changes in the net balance between calcification and organic carbon production. With knowledge of the calcification rate (~5.6 to 10.6 g CaCO 3 m −2 d −1 ) and observed modification in seawater f CO 2 by reef metabolism, rates (—0.6 to 3.3 g C m −2 d −1 ) and seasonal patterns of macroalgal productivity were estimated. Whether the Bermuda coral reef system acts as an oceanic sink or source of CO 2 to the atmosphere not only depends on this seasonal variation, but, more importantly, depends on the pre‐existing air‐sea CO 2 disequilibrium of open ocean waters surrounding the reef system. The Bermuda coral reef system serves as a useful model for understanding the fate of CO 2 in other reefs, particularly those reefs changing because of environmental stress.

Biogeochemical and physical factors influencing seawater ƒCO 2 and air‐sea CO 2 exchange on the Bermuda coral reef - Nicholas R. Bates; Leone Samuels; Liliane Merlivat (Limnology and Oceanography, 2001)
It is uncertain whether coral reef ecosystems are oceanic sources or sinks of carbon dioxide (CO 2 ). Understanding the complex interactions between biogeochemical and physical processes within reef ecosystems is important for determining the contribution of coral reefs to the global carbon cycle and the air‐sea flux of CO2 . The influence of biogeochemical and physical processes on CO 2 cycling was examined for 1 month at Hog Reef Flat, part of the rim reef of Bermuda. The fugacity of seawater CO 2 (CO 2 ) was measured hourly by use of a Carbon Interface Ocean Atmosphere buoy, providing the longest time series of seawater CO 2 data on a coral reef ecosystem. Seawater CO 2 ranged from ~340 to 470 µatm, with a diurnal variability ranging from ~20–60 µatm. Air‐sea CO 2 was directed from ocean to atmosphere with a mean flux of 3.3 ± 4.6 mmoles CO 2 m −2 d −1 . The reef data are compared with a seawater CO 2 time series collected at the U.S. Joint Global Ocean Flux Study Bermuda Atlantic Time‐series Study (BATS) site (31°50'N, 64°10'W) in the Sargasso Sea surrounding Bermuda. Sargasso Sea waters are the original source for Bermuda platform water, providing a context for understanding the biogeochemical modification of reef water at Hog Reef Flat. Seawater fCO 2 at Hog Reef Flat was elevated relative to the Sargasso Sea by ~0 to ~120 µatm, primarily as a result of calcium carbonate production. However, the ability of the reef to act either as a source or sink of CO 2 to/from the atmosphere largely depended on the air‐sea CO 2 disequilibrium of offshore Sargasso Sea waters impinging on the reef site. This study also revealed that an assessment of the fate of CO 2 on coral reefs is dependent on understanding the reef's physical regime and forcing. The dynamics of wind, tide, platform circulation, and fluxes of offshore or onshore waters are necessary context for all coral reef sites.

Building the Long-Term Picture: The U.S. JGOFS Time-Series Programs - David Karl; John Dore; Roger Lukas; Anthony Michaels; Nicholas Bates; Anthony Knap (Oceanography, 2001)

Footprinting of the spinach nitrite reductase gene promoter reveals the preservation of nitrate regulatory elements between fungi and higher plants - Rajeev Rastogi; Nicholas J. Bate; Sobhana Sivasankar; Steven J. Rothstein (Plant Molecular Biology, 1997)